Measuring Persistence in Youth Competencies Development Using Heart Rate Variability (HRV) - Muhammad Nubli, Abdul Wahab; Wan Rusyaini, Wan Mohd (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Persistence or hardworking is a self-regulation, self-control, an attitudes and beliefs pertaining work behavior, effort, strong will and motivational construct. This behavior is an important element for youth to build up their ability in planning and managing their goals. To nurture these positive behaviors, a study needs to be conducted to explore it from the aspect of psychophysiology. The objective of this paper is to measure the level of persistence from the HRV perspective. The Biofeedback Technique has been considered as the best mechanism to measure persistence profile of youth by investigating their level of achievement goal orientation. The subjects were exposed to the method of intrapersonal communication through zikr. The experiments were conducted by investigating their efforts, goal orientation and competence within one’s self to achieve the targeted task. The study conducted involved questionnaires, structured interviews and clinical experiments using the Biofeedback emWave® Desktop Stress Relief System Software equipment. The results from these tests showed that there is a significant relationship between persistence and the HRV spectrum. A hardworking youth have higher HF spectrum compared to the lazy youth. The study shows that the persistence profile can be measured using the psychophysiology technique. This will enhance the individual profiling process that will assist competencies youth development program.